2017
DOI: 10.1002/hep.29176
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy determines efficiency of liver‐directed gene therapy with adeno‐associated viral vectors

Abstract: Use of adeno‐associated viral (AAV) vectors for liver‐directed gene therapy has shown considerable success, particularly in patients with severe hemophilia B. However, the high vector doses required to reach therapeutic levels of transgene expression caused liver inflammation in some patients that selectively destroyed transduced hepatocytes. We hypothesized that such detrimental immune responses can be avoided by enhancing the efficacy of AAV vectors in hepatocytes. Because autophagy is a key liver response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…3 Here, we demonstrated that exosome-enveloped AAV vectors offer a feasible, relatively simple strategy to achieve superior correction of hemophilia via enhanced targeting of hepatocytes, at the same time providing protection from preexisting NAbs. Although the mechanism of enhancement of transduction is not completely understood, based on our in vitro results, exo-AAV vectors seem to present a faster nuclear translocation rate, which may be the result of more efficient and autophagy-independent 22 intracellular trafficking. Additionally, competition experiments presented here suggest that exo-AAV entry occurs through a process dependent on the exosome membrane or protein components (eg, micropinocytosis, receptor-mediated endocytosis), which bypass the need of cell receptor binding of the AAV capsid.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…3 Here, we demonstrated that exosome-enveloped AAV vectors offer a feasible, relatively simple strategy to achieve superior correction of hemophilia via enhanced targeting of hepatocytes, at the same time providing protection from preexisting NAbs. Although the mechanism of enhancement of transduction is not completely understood, based on our in vitro results, exo-AAV vectors seem to present a faster nuclear translocation rate, which may be the result of more efficient and autophagy-independent 22 intracellular trafficking. Additionally, competition experiments presented here suggest that exo-AAV entry occurs through a process dependent on the exosome membrane or protein components (eg, micropinocytosis, receptor-mediated endocytosis), which bypass the need of cell receptor binding of the AAV capsid.…”
Section: Discussionmentioning
confidence: 88%
“…Additional in vitro studies showed that exo-AAV, unlike their standard counterpart, do not seem to rely on autophagy to transduce hepatocytes, 22 as levels of LC3-II were unchanged in cells treated with exo-AAV vectors (supplemental Figure 2A-B). Furthermore, receptor saturation experiments with excess empty capsids showed inhibition of transduction of standard but not exo-AAV vectors (supplemental Figure 2C).…”
Section: Exo-aav Vectors Display Superior In Vitro Transduction Efficmentioning
confidence: 99%
“…Recently, autophagy activation through pharmacological inducers, such as clinically approved rapamycin, has been proven to increase hepatocyte transduction in small- and large-animal models; conversely, its inhibition resulted in decreased levels of AAV transduction. 123 …”
Section: Main Textmentioning
confidence: 99%
“…Since adenoviruses are known to stimulate and exploit the host cell canonical autophagy machinery for their propagation (Hösel et al. 2017 ), limited resources might again be the reason for the increased parasite load, similar to the effect observed upon starvation. It will now be interesting to decipher the molecular details of this complex interplay between distinct autophagy pathways during starvation and virus infection that lead to the increase in parasite survival.…”
Section: Interfering With Autophagy Machinery Has Physiological Consementioning
confidence: 86%